Realisms interlinked objects, subjects and other subjects - Chakrabarti, Arindam (London New York Oxford New Dehli Sydney Bloomsbury Academic, 2021)
"This book brings together over 25 years of Arindam Chakrabarti's original research in East-West 'fusion' philosophy on issues of epistemology, metaphysics, and philosophy of mind. Organized under the three basic concepts of a thing out there in the world, the self who perceives it, and other subjects or selves, his work revolves around a set of realism links. Examining connections between metaphysical stances toward the world, selves, and universals, Chakrabarti engages with classical Indian and modern Western philosophical approaches to a number of live topics including the refutation of idealism; the question of the definability of truth, and the possibility of truths existing unknown to anyone; the existence of non-conceptual perception; and our knowledge of other minds. He additionally makes forays into fundamental questions regarding death, darkness, absence, and nothingness. Together with conceptual clarification and progress towards alternative solutions to these substantial philosophical problems, Chakrabarti demonstrates the advantage of doing philosophy in a cosmopolitan fashion. Beginning with an analysis of the concept of a thing, and ending with an analysis of the concept of nothing, Realisms Interlinked offers a preview of a future metaphysics, epistemology, and philosophy of mind without borders"--
Literaturangaben
Keywords: Realism; Object (Philosophy); Knowledge, Theory of; Metaphysics; Philosophy of Mind; Philosophy, Indic